Young children's enactments of human rights in early childhood education. Issue 1 (2nd January 2016) - Quennerstedt, Ann
ABSTRACT: This paper explores ways in which human rights become part of and affect young children's everyday practices in early childhood education and, more particularly, how very young children enact human rights in the preschool setting. The study is conducted in a Swedish preschool through observations of the everyday practices of a group of children aged between 1 and 3 years. With a child view based on human rights theory and childhood sociology, an action-based methodology for seeking children's perspective is used to analyse the observation data. Three rights areas are identified in which children frequently deal with human rights in their actions and where they enact a range of possible rights holder positions: ownership, influence and equal value. These rights areas, and the children's various enactments of the rights, are reflected against the preschool context as a co-constructor to the actions of the participants.